Village health workers in Bihar, India: an untapped resource in the struggle against kala‐azar. Issue 2 (20th December 2012) - Malaviya, P.; Hasker, E.; Singh, R. P.; Van, J. P.; Boelaert, M.; Sundar, S.
Abstract Introduction In 2005 a visceral leishmaniasis (VL) elimination initiative was launched on the Indian subcontinent; important components of early case finding and treatment are entrusted to the primary health care system (PHC). In an earlier study in Bihar, India, we discovered some major shortcomings in implementation, in particular related to monitoring of treatment and treatment outcomes. These shortcomings could be addressed through involvement of village health workers. In the current study we assessed knowledge, attitude and practice of these village health workers in relation to VL. Main objective was to assess the feasibility of their involvement in VL control. Methods We obtained a list of auxiliary nurses/midwives and accredited social health activists for the highly endemic district of Muzaffarpur. We randomly sampled 100 auxiliary nurses and 100 activists, who were visited in their homes for an interview. Questions were asked on knowledge, attitude and practice related to visceral leishmaniasis and to tuberculosis. Results Auxiliary nurses and activists know the presenting symptoms of visceral leishmaniasis, they know how it is diagnosed but they are not aware of the recommended first‐line treatment. Many are already involved in tuberculosis control and are very well aware of the treatment modalities of tuberculosis, but few are involved in control of visceral leishmaniasis control. They are well organised, have strong links to the primary healthcare system and are ready to get more involved in visceral leishmaniasis control. Conclusion To ensure adequate monitoring of visceral leishmaniasis treatment and treatment outcomes, the control programme urgently needs to consider involving auxiliary nurses and activists.